Costs of Finding an Advanced Adenoma in Colorectal Screening - Jerome B Simon (Canadian Journal of Gastroenterology)
The authors used computerized decision analysis to estimate the costs of finding and removing an advanced colonic adenoma in patients referred because of a positive fecal occult blood test. An advanced adenoma was defined as a villous adenoma, a tubular adenoma 10 mm or more in size, or a lesion that harboured highgrade dysplasia or cancer. Four strategies were compared: flexible sigmoidoscopy, flexible sigmoidoscopy plus air contrast barium enema, virtual colonoscopy (CT colography) and colonoscopy. Colonoscopy with polypectomy was undertaken if any of the methods detected a polyp. Probabilities and test characteristics were determined from the literature, and costs were estimated from the provincial fee schedule (Ontario) and local hospital sources. With an assumed 17% probability of an advanced adenoma being present, sigmoidoscopy was the most cost effective strategy at $1930 to find and clear an advanced lesion, but the procredure missed between one-third and almost one-half of the lesions, depending on the depth of insertion. At $2290, colonoscopy was slightly more expensive than sigmoidoscopy and more cost effective than either sigmoidoscopy plus barium enema ($2840) or virtual colonoscopy ($3681), neither of which detected as many advanced adenomas. The authors concluded that colonoscopy is the preferred investigative strategy and that improved access to colonoscopy is an important goal for occult blood screening programs.